Tvorba riječi u jednom zanimljivom korpusu - Tekavčić, Pavao (Linguistica (Ljubljana), 1998)
The types of word formation in the works of Željka Čorak The article analyzes types of word formation (derivation, composition, prefixation, parasynthetics etc.) in the works of Željka Čorak, an outstanding contemporary Croatian writer. In her texts (from 1970 to 1994), besides the common examples many so-calles ad hoc or individual formations are attested that show both linguistic (and stylistic) creativity of the author and vitality of word formation in present-day standard Croation.
Keywords: Croatian; Čorak, Željka; hrvaščina; hrvaška književnost; neologizmi; tekstna lingvistika